Penguatan nilai-nilai profetik pada peserta didik di Madrasah Manbaul Uloom Malaysia - Abdullah, A. Fatikhul Amin; Thoha, Mohammad; Mukhid, Abdul; Mubah, Hilmi Qosim; Tianah, Itaanis; Ratnawati, Rinta; Busahwi; Kowi, Abdul (PERDIKAN (Journal of Community Engagement), 2024)
The knowledge of prophetic values among the students at Madrasah Manbaul Uloom, based on an interview with Abdul Qowi, the headmaster of the Madrasah, is very low because the students focus more on memorizing the Quran without receiving in-depth religious education. Therefore, an effort must be made to understand and strengthen prophetic values as the main foundation in studying religious knowledge, especially the Quran. Thus, this service is conducted to enhance prophetic values among the students at Madrasah Manbaul Uloom. The method used in this service is the Participatory Action Research method. (PAR). This approach involves students, teachers/ustaz, and the madrasah administration in all stages of the activities, namely 25 students, five teachers, and one administrator. Meanwhile, the improvement efforts involve conducting training and workshops. The results of the service to strengthen prophetic values at Madrasah Manbaul Uloom conducted through training show an apparent increase in understanding of the prophetic values of humanization (amar ma’ruf), liberation (nahi munkar), and transcendence (tu’minuuna billah). The improvement is evident as the students begin to courageously invite their friends to engage in good activities and strive to avoid conflicts among peers. However, there needs to be a follow-up on the periodic improvement of teachers’/ustaz’ competencies to create a more holistic and meaningful learning atmosphere. [Pengetahuan nilai-nilai Profetik Peserta didik di Madrasah Manbaul Uloom berdasarkan hasil wawancara dengan Abdul Qowi selaku Mudir Madrasah sangatlah rendah karena peserta didik lebih fokus belajar menghafal Al Quran tanpa menerima pengajaran agama secara mendalam. Sehingga perlu ada upaya untuk memahamkan dan menguatkan nilai-nilai profetik sebagai landasan utama dalam mempelajari ilmu agama khususnya Al Quran. Maka diadakanlah Pengabdian ini sebagai Upaya meningkatkan nilai-nilai profetik pada peserta didik di Madrasah Manbaul Uloom. Metode yang digunakan pada pengabdian ini adalah metode Participatory Action Research (PAR). Pendekatan ini melibatkan peserta didik/santri, guru/ustaz, dan pihak madrasah dalam seluruh tahapan kegiatan yaitu 25 santri, 5 ustaz, dan 1 pengelola. Sedangkan upaya peningkatannya dengan melakukan pelatihan dan workshop. Hasil dari pengabdian penguatan nilai-nilai profetik di Madrasah Manbaul Uloom yang dilakukan dengan cara pelatihan ini nampak terlihat adanya peningkatan pemahaman tentang nilai-nilai Profetik Humanisasi (amar ma'ruf), Liberasi (nahi munkar), dan Transendensi (tu’minuuna billah). Peningkatan itu nampak pada peserta didik mulai berani mengajak teman-temannya pada hal-hal baik dan berusaha menghindari konflik antar teman. Namun Perlu ada tindak lanjut peningkatan kompetensi guru/ustaz secara berkala agar tercipta suasana pembelajaran yang lebih holistik dan bermakna.]